Myeloid-derived suppressor cells in colorectal cancer: prognostic biomarkers and therapeutic targets - Mohammad A. Al-Mterin; Eyad Elkord (Open Exploration Publishing Inc., 2022)
Myeloid-derived suppressor cells (MDSCs) are a group of immature myeloid cells, which are expanded in most cancer patients. MDSCs suppress host immune responses, leading to cancer growth and progression. Several studies demonstrated that there was a relationship between levels of MDSCs and tumorigenesis in colorectal cancer (CRC) patients. MDSCs are now being investigated for their role as possible therapeutic targets in cancer treatment. This review summarizes available studies that investigated MDSC expansion in CRC patients, as well as their role in CRC tumorigenesis, prognosis, and targeting. Based on the available studies, there is a possible relationship between high levels of MDSCs and CRC progression. Additionally, targeting MDSCs in CRC patients selectively represents a significant challenge for the development of targeted treatments. Targeting of MDSCs could be exploited in different ways including MDSC depletion, inhibition of MDSC function and recruitment, and enhancing MDSC differentiation. Overall, MDSCs could be exploited as prognostic biomarkers and potential therapeutic targets in CRC.